Where I am from matters: factors influencing behavioral and emotional changes in autistic individuals during COVID-19 in Latin America - Montenegro, María Cecilia; Ramírez, Ana C.; Hernandez Rodriguez, Juventino; Villalobos, Bianca T.; Garrido, Gabriela; Amigo, Cecilia; Valdez, Daniel; Barrios, Natalia; Cukier, Sebastián; Rattazzi, Alexia; Rosoli, Analía; García, Ricardo; et al. (Frontiers in Psychiatry, 2023)
We asked 1,743 caregivers of autistic individuals residing in 7 Latin American countries to complete an online survey on perceived changes experienced by their children. We were interested in understanding if autistic individuals living in the COVID-19 pandemic context experienced psychological or behavioral changes based on individual and environmental factors. Our results showed that country of residence predicted increased anxiety and mood changes, as well as more worries about getting sick. Specifically, as reported by caregivers, those who experienced a worsening of family coexistence exhibited increased irritability, aggression, and concentration difficulties. Also, those autistic individuals who increased their screentime utilization experienced more anxiety, and those that were older experienced more preoccupation with getting sick. Our findings show that unhealthy family and child behaviors could place autistic individuals at increased risk for behavioral and psychological changes during the COVID-19 pandemic. This knowledge could help inform policies and decrees aimed at protecting those with neurodevelopmental concerns.